Lithium supplementing material, preparation method thereof, positive electrode sheet and secondary battery

CN116598477BActive Publication Date: 2026-10-23SHENZHEN DYNANONIC INNOVAZONE NEW ENERGY TECH CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310101017.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-19
Publication Date
2026-10-23
Estimated Expiration
2043-01-19

AI Technical Summary

Technical Problem

但是现有的商业硫化锂粉末颗粒大小均在微米级尺寸,内部体积阻碍了硫的转换,从而导致微米级的硫化锂容量较低且势垒较高

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116598477B_ABST
    Figure CN116598477B_ABST
Patent Text Reader

Abstract

The application discloses a lithium supplement material, a preparation method thereof, a positive pole piece and a secondary battery, and belongs to the technical field of lithium supplement materials.The lithium supplement material comprises an inner core and carbon fibers, the inner core is composed of lithium-containing sulfides, the carbon fibers are formed with holes extending from the surface inwards, and the inner core is embedded in the carbon fibers and accommodated in the holes.The lithium supplement material provided by the application has high lithium supplement specific capacity and excellent electronic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of secondary battery technology, specifically to a lithium replenishment material and its preparation method, a positive electrode sheet, and a secondary battery. Background Technology

[0002] Lithium-ion batteries are among the best-performing energy storage and power battery technologies currently available. However, during the initial charging process, lithium ions are transferred from the positive electrode to the negative electrode for storage, accompanied by the formation of a solid electrolyte (SEI) on the surface of the negative electrode. This process irreversibly consumes a portion of the active lithium and reduces the battery's capacity and energy density. Pre-lithiation can introduce additional active lithium into the battery system and shows great promise in compensating for initial lithium loss and increasing the energy density of lithium-ion batteries.

[0003] Nanolithium sulfide is an electrode material with high theoretical capacity and low charging barrier, lower than the cutoff charging potential of many existing cathode materials, allowing for complete lithium delithiation. However, existing commercial lithium sulfide powder particles are all in the micrometer range, and their internal volume hinders sulfur conversion, resulting in lower capacity and higher barrier for micrometer-sized lithium sulfide. Furthermore, the insulating properties of lithium sulfide lead to poor electronic conductivity. Therefore, providing a lithium replenishment material with nanoscale lithium sulfide and excellent electronic conductivity has become a key issue. Summary of the Invention

[0004] The purpose of this application is to provide a lithium supplement material and its preparation method, a positive electrode sheet, and a secondary battery.

[0005] This application provides the following technical solution:

[0006] Firstly, this application provides a lithium replenishment material comprising a core and carbon fibers. The core is composed of lithium-containing sulfides. The carbon fibers have pores extending inward from their surface, and the core is embedded in the carbon fibers and accommodated within the pores. Specifically, the core can be a lithium-containing sulfide with nanoscale dimensions, serving as a lithium source core for lithium replenishment. The carbon fibers can be obtained by carbonizing micro / nano-sized fibers. The carbon fibers can have pores adapted to the size of the core, extending inward from the surface of the carbon fibers. The core is embedded in the carbon fibers, allowing the carbon fibers to partially encapsulate the core. The formation of the carbon fiber pores is due to the reaction between the lithium source and the carbon fiber precursor during the preparation of the lithium replenishment material. When the lithium source is reduced to lithium-containing sulfides, it simultaneously etches the surface of the carbon fibers, thereby embedding the core within the carbon fibers. Optionally, the process of embedding the core into the carbon fiber can be as follows: a polymer solution, lithium sulfate, and micro / nano-sized fibers are uniformly mixed, and then the mixture is sintered to carbonize both the polymer and the micro / nano-sized fibers. Lithium sulfate then undergoes carbothermic reduction with both to produce lithium sulfide. In this process, the carbon source formed by the polymer reacts with the lithium sulfate first and is consumed. The remaining lithium sulfate then reacts with the carbon fiber, consuming the carbon on the carbon fiber surface, and the resulting lithium sulfide is thus embedded within it. It is understandable that multiple uniformly dispersed cores can be embedded in any carbon fiber, forming a beaded structure.

[0007] The lithium replenishment material provided in this application uses lithium-containing sulfides as its core. By embedding the core into carbon fibers through controlled etching, the core is partially coated with carbon fibers. On the one hand, the strong conductivity of carbon fibers enhances the lithium ion transport capability of the lithium replenishment material, overcoming the poor electronic conductivity of lithium-containing sulfides. At the same time, carbon fibers also have a larger specific surface area, which can further improve the lithium ion transport efficiency of the lithium replenishment material. On the other hand, the larger specific surface area of ​​carbon fibers allows the lithium-containing sulfide precursor to have more attachment points during sintering, making the final core less prone to agglomeration. This improves the dispersion of the core and reduces its size. Furthermore, the carbon fiber-coated core structure can reduce the core size to the nanoscale. Utilizing the structural advantages of the nanoscale core, the polarization of the lithium-containing sulfides is smaller, and the voltage plateau during charging is lower. This results in a lower activation barrier for the lithium replenishment material, which can significantly improve the lithium ion insertion / extraction efficiency, thereby achieving a high lithium replenishment specific capacity.

[0008] In one possible implementation, the core is partially embedded in the carbon fiber, with at least a portion protruding from the surface of the carbon fiber; and / or, the core is completely embedded in the carbon fiber and entirely contained within the pore. Specifically, in the core-embedded carbon fiber process provided in the above embodiments, the amount of residual lithium sulfate reacting with the carbon source formed by the polymer during the formation of each core varies, resulting in different amounts of residual lithium sulfate reacting with the carbon fiber. It is understood that when the amount of residual lithium sulfate reacting with the carbon fiber is low, i.e., the etching degree of the carbon fiber is low, the core is mostly partially embedded in the carbon fiber, with a portion exposed outside the carbon fiber and protruding from its surface; when the amount of residual lithium sulfate reacting with the carbon fiber is high, i.e., the etching degree of the carbon fiber is high, the core is mostly completely embedded in the pore, with the core entirely contained within the pore. By setting the core to be partially embedded in the carbon fiber, the amount of precursor used during preparation can be reduced, thereby reducing preparation costs; simultaneously, the preparation difficulty of partially embedded cores is lower, and the formability is easier to control. Setting the core to be completely embedded in the carbon fiber maximizes the contact area between the core and the carbon fiber, thereby providing higher electronic conductivity.

[0009] In one possible implementation, the lithium replenishment material further includes a coating layer covering the outer surface of the core exposed to the external environment. It is understood that since the core is embedded into the carbon fiber through etching, whether semi-embedded or fully embedded, at least part of it is exposed to the external environment. The exposed core readily reacts with water in the environment, thereby reducing the electrochemical performance of the lithium replenishment material. Therefore, a coating layer can be provided on the exposed portion of the core to isolate it from the external environment. Of course, in other implementations, the coating layer can also cover the portion of the core embedded in the carbon fiber. The material of the coating layer can be graphite or other small-sized carbon sources, and there are no specific limitations. By providing a coating layer, not only can the electronic and ionic conductivity of the lithium replenishment material in the core be effectively improved, increasing lithium extraction during charging; it also plays a certain role in isolating moisture, improving the stability of the lithium replenishment material, and achieving a stable lithium replenishment effect. Furthermore, it can also ensure the stability, uniformity of dispersion, and good processing performance of the lithium replenishment material in the electrode active slurry and active layer.

[0010] In one possible implementation, the core is distributed at a density of 10 g / cm³ on a single carbon fiber. 3 ~15g / cm 3 By controlling the distribution density of the core on the carbon fiber within the above range, it is possible to avoid the core being too densely distributed on the carbon fiber, reduce the aggregation of the core on the carbon fiber, and also reduce the occurrence of the core not being embedded in the carbon fiber, ensuring that each carbon fiber can provide a suitable conductive environment for the core.

[0011] In one possible implementation, the carbon fiber accounts for 1% to 5% of the mass of the lithium supplement material. By controlling the distribution density of the core on the carbon fiber within the above range, it is possible to avoid the core being too densely distributed on the carbon fiber, reduce the agglomeration of the core on the carbon fiber, and also reduce the occurrence of the core not being embedded in the carbon fiber, ensuring that each carbon fiber can provide a suitable conductive environment for the core.

[0012] In one possible implementation, the core particle size D50 is 5 nm to 80 nm. Existing commercial lithium sulfide powders typically have particle sizes ranging from 10 μm to 30 μm. Due to their insulating properties, the internal volume of most particles hinders sulfur conversion, resulting in a high potential barrier and low capacity. In this embodiment, the core particle size can be controlled at the nanoscale using a polymer solution. By significantly reducing particle size, achieving a nanoscale core of lithium-containing sulfide can shorten the diffusion length and increase the active specific surface area, which is beneficial for lithium ion insertion and extraction, thereby increasing the capacity of the lithium replenishment material. When the core particle size is smaller than the above range, the preparation difficulty increases, and the particles tend to agglomerate significantly; when the core particle size is larger than the above range, the specific surface area of ​​the core decreases, reducing the lithium ion insertion and extraction efficiency, resulting in poor lithium replenishment performance of the lithium replenishment material.

[0013] In one possible implementation, the diameter of the carbon fiber is 20 nm to 100 nm. Controlling the carbon fiber diameter within this range allows it to adapt to the size of the core, thus facilitating core embedding; simultaneously, it ensures the carbon fiber has a suitable specific surface area, providing an excellent environment for lithium-ion extraction. When the carbon fiber diameter is smaller than this range, the diameter is too small, making it easy for the core to penetrate the carbon fiber, thereby reducing the carbon fiber's coverage area over the core; when the carbon fiber diameter is larger than this range, the specific surface area of ​​the carbon fiber decreases, which is detrimental to lithium-ion extraction.

[0014] In one possible implementation, the length of the carbon fiber is 1 μm to 20 μm. Controlling the length of the carbon fiber within this range not only facilitates the full dispersion of the fiber during the preparation process and avoids entanglement due to excessive fiber length, but also helps to increase the contact area between the carbon fiber and the core, resulting in a more uniform distribution of the core on the carbon fiber and controlling the density distribution of the core on the carbon fiber.

[0015] In one possible implementation, the aperture's outline is spherical, hemispherical, or ellipsoidal. Understandably, by controlling the core size to the nanometer scale using a polymer solution, the core shape is mostly spherical or near-spherical. Since the aperture is formed by etching the inner shell, the aperture's outline should match the inner shape. When the core is fully embedded in the carbon fiber, the aperture shape can be spherical or ellipsoidal; when the core is partially embedded in the carbon fiber, the aperture shape can be hemispherical.

[0016] In one possible implementation, the pore size is 5 nm to 80 nm. It is understood that the pore size can be referenced to the kernel particle size in the above embodiments, and will not be elaborated further here.

[0017] In one possible implementation, the volume of the pores accounts for 40%-70% of the volume of the carbon fiber. Understandably, the volume of the pores refers to the space occupied by the pores on the encapsulation layer. As can be seen from the above implementation, the volume ratio of the pores should be related to the distribution density of the core on the carbon fiber. If the volume ratio of the pores is controlled within the above range, it indicates that the distribution density of the core on the carbon fiber is moderate, and the depth of the core embedded in the carbon fiber is appropriate. When the volume ratio of the pores is too small, it indicates that the distribution of the core on the carbon fiber is sparse, and the core is free outside the carbon fiber, which can easily prevent the carbon fiber from performing its conductive function; it may also be that the core is embedded too shallowly, causing the core to easily detach, thereby affecting the electrochemical performance.

[0018] In one possible implementation, the thickness of the coating layer is 10 nm to 100 nm. Understandably, the thickness of the coating layer simultaneously ensures both the specific capacity and electronic conductivity environment of the lithium-filling material. When the coating layer thickness is less than the above range, the coating layer does not completely cover the core, which is detrimental to constructing a good electronic conductivity environment; when the coating layer thickness is greater than the above range, since the coating layer does not contribute lithium ions, it will reduce the overall added specific capacity.

[0019] In one possible implementation, the coating layer comprises 2% to 5% of the lithium replenishment material by mass. By controlling the proportion of the coating layer in the lithium replenishment material, it is possible not only to ensure that the coating layer fully covers the portion of the core exposed to the external environment, thereby avoiding the influence of water and carbon dioxide in the external environment on the core, but also to provide the core with excellent specific capacity and electronic conductivity environment. If the mass proportion of the coating layer is too high, the overall added specific capacity will be reduced because the coating layer does not contribute lithium ions; if the mass proportion of the coating layer is too low, it is not conducive to forming a complete and uniform coating layer on the outer surface of the core, resulting in incomplete coating and hindering the construction of a good electronic conductivity environment.

[0020] In one possible implementation, the chemical formula of the lithium-containing sulfide includes Li x Sy , where 1≤x≤2, 1≤y≤6.

[0021] Secondly, this application also provides a method for preparing a lithium supplement material, comprising: mixing a lithium-containing sulfide precursor, a polymer precursor and a carbon fiber precursor, and obtaining a precursor mixture after shaping; sintering the precursor mixture to obtain the lithium supplement material, wherein the lithium supplement material comprises a core and carbon fibers, the carbon fibers having pores extending from the surface inward, and the core being embedded in the pores of the carbon fibers.

[0022] In one possible implementation, after sintering the precursor mixture to obtain the lithium replenishing material, the process further includes: mixing and sintering the lithium replenishing material and a carbon source, wherein the carbon source forms a coating layer covering the outer surface of the core exposed to the external environment.

[0023] Thirdly, this application also provides a positive electrode sheet, the positive electrode sheet comprising a current collector and an active material layer disposed on the current collector, the active material layer comprising a positive electrode material and a lithium supplement material as described in any one of the embodiments of the first aspect, or the active material layer comprising a lithium supplement material obtained by a method for preparing a positive electrode material and a lithium supplement material as described in any one of the embodiments of the second aspect.

[0024] Fourthly, this application also provides a secondary battery, including the positive electrode sheet described in the third aspect, or the battery including the lithium replenishing material described in any one of the embodiments of the first aspect, or the battery including the lithium replenishing material obtained by the preparation method of the lithium replenishing material described in any one of the embodiments of the second aspect. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0026] Figure 1 This is a schematic diagram of the appearance of the lithium replenishment material in one embodiment;

[0027] Figure 2 This is a schematic cross-sectional view of a core portion embedded with carbon fiber in one embodiment.

[0028] Figure 3 This is a schematic cross-sectional view of one embodiment where the core is entirely embedded in carbon fiber;

[0029] Figure 4This is a schematic cross-sectional view of the lithium replenishment material in one embodiment;

[0030] Figure 5 This is a flowchart of a method for preparing lithium-supplementing materials in one embodiment. Detailed Implementation

[0031] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0032] It should be noted that when a component is said to be "fixed" to another component, it can be directly on the other component or it can be in a middle component. When a component is said to be "connected" to another component, it can be directly connected to the other component or it may be in a middle component.

[0033] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used in this application's specification is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used in this application includes any and all combinations of one or more of the associated listed items.

[0034] The following detailed description of some embodiments of this application is provided in conjunction with the accompanying drawings. Unless otherwise specified, the following embodiments and features can be combined with each other.

[0035] Firstly, this application provides a lithium replenishment material 100, please refer to... Figure 1 , Figure 2 and Figure 4 The lithium replenishment material 100 includes a core 10 and a carbon fiber 20. The core 10 is composed of lithium-containing sulfides and has a nanoscale size. The carbon fiber 20 has pores 21 extending from the surface inward. The core 10 is embedded in the carbon fiber 20 and accommodated in the pores 21.

[0036] Specifically, the core 10 can be a lithium-containing sulfide with nanoscale dimensions, serving as the lithium source core for lithium replenishment. Optionally, the lithium-containing sulfide can be lithium sulfide, and its precursor can be lithium sulfate. Adding the lithium-containing sulfide core 100 as the lithium replenishment material 100 to the electrode allows it to act as a "sacrificial agent" during the first charging cycle, releasing as many lithium ions as possible at once to replenish the irreversible lithium ions consumed in the formation of the SEI film at the negative electrode. This maintains an ample supply of lithium ions within the battery system, improving the battery's initial efficiency and overall electrochemical performance. Compared to other lithium replenishment materials 100, the lithium-containing sulfide compound-based material 100 exhibits weaker binding forces between lithium ions and sulfur ions, lower polarization, and a lower voltage plateau during charging. This effectively reduces the activation barrier of the lithium-containing sulfide compound, significantly improving the lithium ion insertion / extraction efficiency, thus enabling the lithium replenishment material 100 to possess a higher specific capacity for lithium replenishment. Furthermore, lithium-containing sulfur compounds do not produce oxygen during lithium replenishment, reducing the risk of gas buildup in lithium batteries. Simultaneously, the lithium polysulfides formed after delithiation of lithium-containing sulfur compounds can diffuse to the negative electrode, alleviating lithium plating issues at the negative electrode.

[0037] Carbon fiber 20 can be obtained by carbonization of micro / nano-sized fibers. The carbon fiber 20 may have pores 21 adapted to the size of the core 10, extending from the surface of the carbon fiber 20 inwards. The core 10 is embedded within the carbon fiber 20, allowing the carbon fiber 20 to partially encapsulate the core 10. The formation of the pores 21 in the carbon fiber 20 may be due to the reaction between the lithium source and the precursor of the carbon fiber 20 during the preparation of the lithium supplement material 100. This reaction allows the lithium source to simultaneously etch the surface of the carbon fiber 20 when reduced to a lithium-containing sulfide, thereby embedding the carbon fiber 20 within it.

[0038] Optionally, the process of embedding the core 10 into the carbon fiber 20 can be as follows: a polymer solution, lithium sulfate, and micro / nano-sized fibers are uniformly mixed, and then the mixture is sintered to carbonize the polymer and the micro / nano-sized fibers. Then, lithium sulfate undergoes carbothermic reduction with both to produce lithium sulfide. In this process, the carbon source formed by the polymer reacts with the lithium sulfate first and is consumed. The remaining lithium sulfate then reacts with the carbon fiber 20, consuming the carbon on the surface of the carbon fiber 20, and the resulting lithium sulfide is thus embedded within it. It is understood that multiple uniformly dispersed cores 10 can be embedded in any carbon fiber 20, forming a beaded structure on the carbon fiber 20.

[0039] The lithium replenishment material 100 provided in this application uses a lithium-containing sulfide as its core 10. The core 10 is embedded into carbon fiber 20 through controlled etching, and the carbon fiber 20 partially coats the core 10. On the one hand, the strong conductivity of the carbon fiber 20 enhances the lithium replenishment material 100's ability to transport lithium ions, overcoming the poor electronic conductivity of the lithium-containing sulfide. Simultaneously, the carbon fiber 20 has a larger specific surface area, further improving the lithium ion transport efficiency of the lithium replenishment material 100. On the other hand, the larger specific surface area of ​​the carbon fiber 20 allows the lithium-containing sulfide precursor to... During the sintering process, the body can have more attachment points, and the resulting core 10 is less prone to agglomeration. This improves the dispersibility of the core 10 while reducing its size. Furthermore, by coating the core 10 with carbon fiber 20, the core 10 can be reduced to the nanoscale size. Utilizing the structural advantages of the nanoscale core 10, the polarization of lithium sulfides is smaller, and the voltage plateau during charging is lower. This allows the lithium replenishment material 100 to have a lower activation barrier, which can significantly improve the lithium ion insertion / extraction efficiency, thereby achieving a higher lithium replenishment specific capacity of the lithium replenishment material 100.

[0040] In one possible implementation, please refer to Figures 1 to 3 The core 10 is partially embedded in the carbon fiber 20, with at least a portion protruding from the surface of the carbon fiber 20; and / or, the core 10 is completely embedded in the carbon fiber 20 and entirely contained within the cavity 21. Specifically, in the specific process of embedding the core 10 into the carbon fiber 20 provided in the above embodiments, since the amount of reaction between each core 10 and the carbon source formed by the polymer during the formation process is different, the amount of remaining lithium sulfate reacting with the carbon fiber 20 will also vary. It is understood that when the amount of remaining lithium sulfate reacting with the carbon fiber 20 is small, that is, the degree of etching of the carbon fiber 20 is low, the core 10 is mostly partially embedded in the carbon fiber 20, with a portion exposed outside the carbon fiber 20 and protruding from the surface of the carbon fiber 20; when the amount of remaining lithium sulfate reacting with the carbon fiber 20 is large, that is, the degree of etching of the carbon fiber 20 is high, the core 10 is mostly completely embedded in the cavity 21, and the core 10 is completely contained within the cavity 21.

[0041] Optionally, the core 10 can be controlled to be either a semi-embedded or fully embedded aperture 21 by adjusting the concentration of the polymer solution. When the polymer solution concentration is low, the core 10 is mostly fully embedded in the aperture 21, while when the polymer solution concentration is high, the core 10 is mostly semi-embedded in the aperture 21.

[0042] By partially embedding carbon fiber 20 into the core 10, the amount of precursor used during preparation can be reduced, thereby reducing preparation costs. Furthermore, partially embedding carbon fiber 20 into the core 10 makes preparation easier and allows for better control of its formability. Conversely, fully embedding carbon fiber 20 into the core 10 maximizes the contact area between the core 10 and the carbon fiber 20, thus providing higher electronic conductivity.

[0043] In one possible implementation, please refer to Figure 2 and Figure 3 The lithium replenishment material 100 also includes a coating layer 30, which covers the outer surface of the core 10 exposed to the external environment. Understandably, since the core 10 is embedded into the carbon fiber 20 by etching, whether it is partially embedded in the hole 21 or fully embedded in the hole 21, at least part of it is exposed to the external environment. The core 10 exposed to the external environment is highly susceptible to reaction with water and carbon dioxide, thereby reducing the electrochemical performance of the lithium replenishment material 100. Therefore, a coating layer 30 can be provided on the exposed portion of the core 10 to isolate the core 10 from the external environment. Of course, in other embodiments, the coating layer 30 can also cover the portion of the core 10 embedded in the carbon fiber. The material of the coating layer 30 can be graphite or other small-sized carbon sources, and there are no specific limitations. By providing the coating layer 30, not only can the electronic and ion conduction performance of the lithium replenishment material 100 in the core 10 be effectively improved, increasing lithium extraction during charging; it can also play a certain role in isolating moisture, improving the stability of the lithium replenishment material 100, and achieving a stable lithium replenishment effect. In addition, it can also ensure the stability, uniformity of dispersion, and good processing performance of lithium replenishment material 100 in electrode active slurry and active layer.

[0044] In one possible implementation, the core is distributed at a density of 10 g / cm³ on a single carbon fiber. 3 ~15g / cm 3 Specifically, the core density distributed on a single carbon fiber can be, but is not limited to, 10 g / cm³. 3 11g / cm 3 12g / cm 3 13g / cm 3 14g / cm 3 15g / cm 3 By controlling the distribution density of the core on the carbon fiber within the above range, it is possible to avoid the core being too densely distributed on the carbon fiber, reduce the aggregation of the core on the carbon fiber, and also reduce the occurrence of the core not being embedded in the carbon fiber, ensuring that each carbon fiber can provide a suitable conductive environment for the core.

[0045] In one possible implementation, the carbon fiber accounts for 1% to 5% of the mass of the lithium supplement material. By controlling the distribution density of the core on the carbon fiber within the above range, it is possible to avoid the core being too densely distributed on the carbon fiber, reduce the agglomeration of the core on the carbon fiber, and also reduce the occurrence of the core not being embedded in the carbon fiber, ensuring that each carbon fiber can provide a suitable conductive environment for the core.

[0046] In one possible implementation, the core particle size D50 is 5 nm to 80 nm. Specifically, the core particle size can be, but is not limited to, 5 nm, 10 nm, 15 nm, 20 nm, 30 nm, 50 nm, and 80 nm. Existing commercial lithium sulfide powders typically have particle sizes of 10 μm to 30 μm. Due to their insulating properties, the internal volume of most particles hinders sulfur conversion, resulting in a high potential barrier and low capacity. In the embodiments of this application, the core particle size can be controlled at the nanoscale using a polymer solution. By significantly reducing the particle size, achieving a nanoscale core of lithium-containing sulfide can shorten the diffusion length and increase the active specific surface area, which is beneficial for lithium ion insertion and extraction, thereby increasing the capacity of the lithium replenishment material. When the core particle size is smaller than the above range, the preparation difficulty increases, and the particles tend to agglomerate significantly; when the core particle size is larger than the above range, the specific surface area of ​​the core decreases, reducing the lithium ion insertion and extraction efficiency, resulting in poor lithium replenishment performance of the lithium replenishment material.

[0047] In one possible implementation, the diameter of the carbon fiber is 20 nm to 100 nm. Specifically, the diameter of the carbon fiber can be, but is not limited to, 20 nm, 25 nm, 30 nm, 40 nm, 60 nm, 80 nm, and 100 nm. Controlling the diameter of the carbon fiber within this range allows it to adapt to the size of the core, thus facilitating core embedding; simultaneously, it ensures the carbon fiber has a suitable specific surface area, providing an excellent environment for lithium-ion extraction. When the diameter of the carbon fiber is smaller than the above range, the diameter is too small, making it easy for the core to penetrate the carbon fiber, thereby reducing the area of ​​the carbon fiber covering the core; when the diameter of the carbon fiber is larger than the above range, the specific surface area of ​​the carbon fiber decreases, which is not conducive to lithium-ion extraction.

[0048] In one possible implementation, the length of the carbon fiber is 1 μm to 20 μm. Specifically, the length of the carbon fiber can be, but is not limited to, 1 μm, 3 μm, 5 μm, 10 μm, 15 μm, or 20 μm. Controlling the length of the carbon fiber within the above range not only facilitates the full dispersion of the fiber during the preparation process and avoids entanglement due to excessive fiber length, but also helps to increase the contact area between the carbon fiber and the core, resulting in a more uniform distribution of the core on the carbon fiber and controlling the density distribution of the core on the carbon fiber.

[0049] In one possible implementation, the aperture's outline is spherical, hemispherical, or ellipsoidal. Understandably, by controlling the core size to the nanometer scale using a polymer solution, the core shape is mostly spherical or near-spherical. Since the aperture is formed by etching the inner shell, the aperture's outline should match the inner shape. When the core is fully embedded in the carbon fiber, the aperture shape can be spherical or ellipsoidal; when the core is partially embedded in the carbon fiber, the aperture shape can be hemispherical.

[0050] In one possible implementation, the pore size is 5nm to 80nm. Specifically, the pore size can be, but is not limited to, 5nm, 10nm, 15nm, 20nm, 30nm, 50nm, or 80nm. It is understood that the pore size can be referenced to the kernel particle size in the above implementation, and will not be elaborated upon here.

[0051] In one possible implementation, the volume of the pores accounts for 40%-70% of the carbon fiber volume. Understandably, the volume of the pores refers to the space occupied by the pores on the encapsulation layer. As can be seen from the above implementation, the volume ratio of the pores should be related to the distribution density of the core on the carbon fiber. If the volume ratio of the pores is controlled within the above range, it indicates that the distribution density of the core on the carbon fiber is moderate, and the depth of the core embedded in the carbon fiber is appropriate. When the volume ratio of the pores is too small, it indicates that the core distribution on the carbon fiber is sparse, and the core is free outside the carbon fiber, which can easily prevent the carbon fiber from performing its conductive function; it may also be that the core embedding depth is too shallow, causing the core to easily detach, thereby affecting the electrochemical performance.

[0052] In one possible implementation, the thickness of the coating layer is 10 nm to 100 nm. Specifically, the thickness of the coating layer can be, but is not limited to, 10 nm, 15 nm, 20 nm, 40 nm, 60 nm, 80 nm, and 100 nm. Understandably, the thickness of the coating layer simultaneously ensures the specific capacity and electronic conductivity environment of the lithium-filling material. When the coating layer thickness is less than the above range, the coating layer does not completely cover the core, which is not conducive to building a good electronic conductivity environment; when the coating layer thickness is greater than the above range, since the coating layer does not contribute lithium ions, it will reduce the overall added specific capacity.

[0053] In one possible implementation, the coating layer accounts for 2% to 5% of the mass of the lithium replenishment material. By controlling the proportion of the coating layer in the lithium replenishment material, it is possible not only to ensure that the coating layer fully covers the portion of the core exposed to the external environment, thereby avoiding the influence of water and carbon dioxide in the external environment on the core, but also to provide the core with excellent specific capacity and electronic conductivity environment. If the mass proportion of the coating layer is too high, the overall added specific capacity will be reduced because the coating layer does not contribute lithium ions; if the mass proportion of the coating layer is too low, it is not conducive to forming a complete and uniform coating layer on the outer surface of the core, resulting in incomplete coating and hindering the construction of a good electronic conductivity environment.

[0054] In one possible implementation, the chemical formula of the lithium-containing sulfide includes Li x S y Where 1≤x≤2, 1≤y≤6. Specifically, the chemical formula of lithium sulfides can be, but is not limited to, Li2S, Li2S2, Li2S4, and Li2S6.

[0055] Secondly, this application also provides a method for preparing a lithium-supplementing material, please refer to... Figure 5 Specifically, it is used in the preparation of the lithium supplementation material in the first aspect. Its preparation method includes the following steps:

[0056] Step S10: The lithium sulfide precursor, polymer precursor and carbon fiber precursor are mixed and shaped to obtain a precursor mixture.

[0057] Step S20: The precursor mixture is sintered to obtain a lithium replenishing material. The lithium replenishing material includes a core and carbon fibers. The carbon fibers have pores extending from the surface inward, and the core is embedded in the pores of the carbon fibers.

[0058] In step S30, after mixing and sintering the lithium replenishment material and the carbon source, the carbon source forms a coating layer that covers the outer surface of the core exposed to the external environment.

[0059] Specifically, the principle and specific process of preparing lithium sulfide using polymer precursors and carbon fiber precursors can be referred to the above implementation method.

[0060] In one possible implementation, in step S10 above, the lithium sulfide precursor can be a lithium sulfate solution; the concentration of the lithium sulfate solution is 0.5 mol / L to 5 mol / L.

[0061] In one possible implementation, in step S10 above, the polymer precursor can be polyethylene oxide (PEO), polyvinyl pyrrolidone (PVP), polyacrylamide (PAM), etc. Preferably, the polymer precursor is a water-soluble polymer. Water-soluble polymers are chosen because they can be directly mixed with lithium sulfate solution without the need for additional organic solvents. Furthermore, water-soluble polymers have strong dispersing properties; most water-soluble polymers contain hydrophilic groups and a certain number of hydrophobic groups, making it easy for them to adsorb onto the outer surface of particles to form a shell, shielding the particles from aggregation. Therefore, using water-soluble polymers as precursors makes it easier to obtain a core of lithium sulfides with nanoscale dimensions.

[0062] In one possible implementation, the amount of polymer precursor added is 0.5g-5g.

[0063] In one possible implementation, in step S10 above, the carbon fiber precursor can be a natural fiber or an artificial fiber. The natural fiber can be bacterial cellulose, and the artificial fiber can be polyacrylonitrile fiber. The preparation methods of the artificial fiber include, but are not limited to, stretching, template synthesis, self-assembly, microphase separation, and electrospinning. It is understood that the diameter of the selected carbon fiber precursor can be slightly larger than the diameter of the carbon fiber provided in the above embodiments. This is because during the carbonization process of the carbon fiber precursor, all atoms except carbon atoms will separate due to heat, resulting in a shrinkage of the final carbon fiber diameter. Therefore, to ensure that the final carbon fiber diameter is controlled within the aforementioned range, a precursor with a slightly larger diameter can be selected. Simultaneously, the length of the carbon fiber precursor can also be slightly larger than the length of the carbon fiber provided in the above embodiments.

[0064] In one possible implementation, the amount of carbon fiber precursor added is 1g-5g.

[0065] In one possible implementation, in step S10 above, the shaping method can be freeze drying or extrusion drying.

[0066] In one possible implementation, in step S20 above, the sintering temperature of the precursor mixture can be 600℃~800℃, and the sintering time can be 5h~10h.

[0067] In one possible implementation, in step S20 above, the sintering environment of the precursor mixture can be an atmosphere formed by any of the protective gases among nitrogen, argon, and a nitrogen-argon mixture.

[0068] In one possible implementation, step S30 further includes crushing and grinding the lithium replenishing material obtained in step S20; then the mixing ratio with the carbon source can be 50:1 to 20:1, and the two are fully mixed by solid-phase mixing ball milling, and the carbon source can be firmly coated on the surface of the core by secondary sintering.

[0069] Thirdly, this application also provides a positive electrode sheet, which includes a current collector and an active material layer disposed on the current collector. The active material layer includes a positive electrode material and a lithium replenishment material as described in the first aspect, or the active material layer includes a lithium replenishment material obtained by a method for preparing a positive electrode material and a lithium replenishment material as described in the second aspect. The positive electrode sheet provided by this application, because it contains the aforementioned lithium replenishment material, and this lithium replenishment material can provide compensation for the active lithium ions consumed during the first charge of the battery due to the formation of the SEI film, effectively maintains the specific capacity of the positive electrode sheet and improves the capacity retention rate of the positive electrode sheet. Simultaneously, the lithium replenishment material can release lithium polysulfides to eliminate lithium plating, which not only maintains the performance of the positive electrode sheet but also improves its service life.

[0070] In one possible embodiment, the positive electrode includes a positive current collector, on which a positive active layer is formed. The positive active layer includes components such as a positive electrode material, a conductive agent, and a binder. This application does not specifically limit these materials; suitable materials can be selected according to actual application requirements. The positive current collector includes, but is not limited to, any one of copper foil and aluminum foil. The positive active material can be a phosphate positive active material or a ternary positive active material. In specific embodiments, it includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxide phosphate, lithium fluorinated vanadium phosphate, lithium titanate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide. The conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60, and carbon nanotubes, and the content of the conductive agent in the positive active layer is 3wt%-5wt%. The types of binders include one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethylcellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives, and the content of the binder in the positive electrode active layer is 2wt%-4wt%.

[0071] In one possible implementation, the content of the lithium replenishing material in the positive electrode material can be controlled at 1%-6% of the mass of the positive electrode active material. This ratio can precisely compensate for the loss of active lithium during the first charge of the battery. If the amount of lithium replenishing material added to the positive electrode is too low, the lost active lithium in the positive electrode material cannot be fully replenished, which is not conducive to improving the energy density and capacity retention of the battery. If the amount of lithium replenishing material added to the positive electrode material is too high, it may cause severe lithium plating on the negative electrode and increase costs. In some specific embodiments, the mass percentage of the lithium replenishing material in the positive electrode material can be 1%, 2%, 4%, 6%, etc.

[0072] Fourthly, this application also provides a secondary battery comprising the aforementioned positive electrode. The addition of the aforementioned lithium-replenishing material to the positive electrode effectively compensates for the active lithium ions consumed during the first charge due to the formation of the SEI film, effectively maintaining the specific capacity of the positive electrode and improving its capacity retention rate. Simultaneously, it also maintains the shape of the secondary battery, improving its lifespan. Furthermore, due to the elimination of lithium plating, it also increases the charging capacity of the secondary battery and reduces the possibility of spontaneous combustion.

[0073] The technical solution of the present invention will be described in detail below through specific embodiments.

[0074] Example 1

[0075] This embodiment provides a lithium replenishing material and its preparation method. The lithium replenishing material includes a core, carbon fibers, and a coating layer. The core is embedded in the carbon fibers, and the coating layer covers the exposed outer surface of the core. The core is Li2S.

[0076] The preparation method of this lithium supplement material includes the following steps:

[0077] (1) Polyethylene oxide and bacterial cellulose were added to a lithium sulfate solution and then freeze-dried to obtain a precursor mixture; wherein the concentration of the lithium sulfate solution was 2 mol / L and the volume was 200 mL, the mass of the polyethylene oxide was 12 g, and the mass of the bacterial cellulose was 0.5 g.

[0078] (2) The precursor mixture was placed in a tube furnace and sintered in an argon atmosphere at 700°C for 3 hours to obtain carbon fibers and Li2S cores embedded in the carbon fibers.

[0079] (3) The sintered material is placed in a glove box for crushing and grinding, and then mixed with conductive carbon black solid phase and ball-milled for 2 hours. Then it is placed in a tube furnace for secondary sintering to finally obtain the lithium supplement material. The mixing ratio is 30:1, and the secondary sintering is sintering in an argon atmosphere at 500°C for 2 hours.

[0080] In the lithium replenishment material, the core particle size D50 is 30nm, the carbon fiber diameter is 60nm, the carbon fiber length is 1μm, and the coating thickness is 60nm.

[0081] Example 2

[0082] This embodiment provides a lithium replenishing material and its preparation method. The lithium replenishing material includes a core, carbon fibers, and a coating layer. The core is embedded in the carbon fibers, and the coating layer covers the exposed outer surface of the core. The core is Li2S.

[0083] The preparation method of this cathode material includes the following steps:

[0084] (1) Same as step (1) in Example 1;

[0085] (2) The difference from step (2) in Example 1 is that the sintering temperature is 650°C;

[0086] (3) is the same as step (3) in Example 1.

[0087] In the lithium replenishment material, the core particle size D50 is 10nm, the carbon fiber diameter is 60nm, the carbon fiber length is 1μm, and the coating thickness is 60nm.

[0088] Example 3

[0089] This embodiment provides a lithium replenishing material and its preparation method. The lithium replenishing material includes a core, carbon fibers, and a coating layer. The core is embedded in the carbon fibers, and the coating layer covers the exposed outer surface of the core. The core is Li2S.

[0090] The preparation method of this cathode material includes the following steps:

[0091] (1) Same as step (1) in Example 1;

[0092] (2) The difference from step (2) in Example 1 is that the sintering temperature is 750°C;

[0093] (3) is the same as step (3) in Example 1.

[0094] In the lithium replenishment material, the core particle size D50 is 80nm, the carbon fiber diameter is 60nm, the carbon fiber length is 1μm, and the coating thickness is 60nm.

[0095] Example 4

[0096] This embodiment provides a lithium replenishing material and its preparation method. The lithium replenishing material includes a core, carbon fibers, and a coating layer. The core is embedded in the carbon fibers, and the coating layer covers the exposed outer surface of the core. The core is Li2S.

[0097] The preparation method of this cathode material includes the following steps:

[0098] (1) Same as step (1) in Example 1;

[0099] (2) Unlike step (2) in Example 1, the sintering temperature is 800℃;

[0100] (3) is the same as step (3) in Example 1.

[0101] In the lithium replenishment material, the core particle size D50 is 200nm, the carbon fiber diameter is 60nm, the carbon fiber length is 1μm, and the coating thickness is 60nm.

[0102] Example 5

[0103] This embodiment provides a lithium replenishing material and its preparation method. The lithium replenishing material includes a core, carbon fibers, and a coating layer. The core is embedded in the carbon fibers, and the coating layer covers the exposed outer surface of the core. The core is Li2S.

[0104] The preparation method of this cathode material includes the following steps:

[0105] (1) Same as step (1) in Example 1;

[0106] (2) Same as step (2) in Example 1;

[0107] (3) The difference from step (3) in Example 1 is that only grinding and sieving are performed, without mixing with conductive carbon black solid phase for ball milling and secondary sintering.

[0108] In the lithium replenishment material, the core particle size D50 is 30nm, the carbon fiber diameter is 60nm, the carbon fiber length is 1μm, and the coating thickness is 0nm.

[0109] Comparative Example 1

[0110] The difference between the positive electrode lithium replenishment material in this comparative example and that in Example 1 is:

[0111] Unlike steps (1) and (2) in Example 1, it is not necessary to prepare the precursor by carbothermal reduction, and the core is directly made of commercially available micron-sized lithium sulfide;

[0112] The same as step (3) in Example 1.

[0113] In the lithium replenishment material, the core particle size D50 is 2 μm, and the coating thickness is 60 nm.

[0114] The lithium replenishment materials provided in Examples 1 to 5 and the lithium replenishment material provided in Comparative Example 1 were assembled into lithium sulfide cathodes, inter-matched cathode electrodes, and lithium-ion batteries respectively according to the following methods:

[0115] Lithium sulfide cathode: The lithium supplement material is mixed with polyvinylidene fluoride and SP-Li in a mass ratio of 80:8:12 and ball-milled to obtain a cathode slurry. The cathode slurry is coated on the surface of aluminum foil, vacuum dried at 110°C overnight, and rolled to obtain a cathode sheet.

[0116] Compatible positive electrode: The lithium supplement material and lithium iron phosphate are mixed at a mass ratio of 4:96 to obtain a mixture. The mixture is then mixed with polyvinylidene fluoride and SP-Li at a mass ratio of 93:3:4 and ball-milled to obtain a positive electrode slurry. The positive electrode slurry is coated on the surface of aluminum foil, vacuum dried at 110°C overnight, and rolled to obtain a positive electrode sheet.

[0117] Negative electrode: Graphite, carboxymethyl cellulose (CMC), SBR and SP are mixed and ball-milled in a mass ratio of 95.8:1.2:2:1 to obtain a negative electrode slurry. The negative electrode slurry is coated on the surface of copper foil and dried under vacuum at 110°C overnight to obtain a negative electrode sheet.

[0118] Electrolyte: Ethyl carbonate and methyl ethyl carbonate are mixed in a volume ratio of 3:7, and LiPF6 is added to form an electrolyte with a concentration of 1 mol / L.

[0119] Diaphragm: Polypropylene microporous diaphragm;

[0120] Lithium-ion battery assembly: Assemble button-type lithium-ion full cells in an inert atmosphere glove box according to the assembly sequence of graphite negative electrode sheet - separator - electrolyte - positive electrode sheet.

[0121] The electrochemical performance of each lithium-ion battery assembled in the above lithium-ion battery examples was tested as shown in Table 1. The test results are shown in Table 1 below:

[0122] Table 1

[0123]

[0124] As can be seen from the test results of Examples 1-5 and Comparative Example 1 in Table 1, the method provided in this application for treating and coating the lithium sulfide core can not only significantly reduce the core grain size, but also increase the electrochemical performance of the assembled lithium-ion battery by introducing carbon fibers. The specific capacity of the lithium-ion battery is significantly improved, and the diffusion coefficient of lithium ions is significantly increased with the introduction of carbon fibers. As can be seen from the test results of Examples 1-4 in Table 1, the grain size of the lithium sulfide core also has a significant impact on the electrochemical performance of the lithium-ion battery. The smaller the grain size of the core, the better the chemical performance of the assembled lithium-ion battery. Smaller particle size is conducive to the release of internal lithium ions and also more conducive to their embedding into carbon fibers with a diameter of nanometers. This greatly enhances the electronic and ionic conductivity of the positive electrode, thus the positive electrode capacity is also fully released. A suitable carbon coating layer can not only improve conductivity, but also inhibit the reaction of trace moisture in the positive electrode and electrolyte, thus maintaining capacity. Meanwhile, the grain size of the core is also affected by the sintering temperature. The lower the sintering temperature, the smaller the grain size of the core. This is because the sintering temperature affects the carbonization of the polymer precursor and micro / nano fibers, thereby affecting the degree of carbothermic reaction between the polymer precursor and lithium sulfate. Therefore, the grain size of the core can be controlled by controlling the sintering temperature.

[0125] In summary, by using a polymer precursor mixed with lithium sulfate for pre-coating, the size of the lithium sulfide core can be significantly reduced, achieving a nanoscale and thus high theoretical capacity. Furthermore, compared to expensive commercial lithium sulfide, this application utilizes the carbothermic reduction of lithium sulfate to lithium sulfide, significantly reducing costs and facilitating large-scale industrialization. Secondly, by controlling the etching and embedding of carbon fibers into the core, the poor electronic conductivity of lithium sulfide is overcome, and the core dispersion is improved. Finally, the carbon coating layer prevents the un-embedded carbon fiber portion of the core from being directly exposed to air, isolating moisture and reducing hydrogen sulfide generation, thus contributing to maintaining high capacity.

[0126] In the description of the embodiments of this application, it should be noted that the orientation or positional relationship of the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer" and other indicators are based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of describing this application and simplifying the description, and are not intended to indicate or imply that the device or component referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this application.

[0127] The above-disclosed embodiments are merely preferred embodiments of this application and should not be construed as limiting the scope of this application. Those skilled in the art will understand that all or part of the processes for implementing the above embodiments and equivalent variations made in accordance with the claims of this application are still within the scope of this application.

Claims

1. A lithium supplementation material, characterized in that, include: The core is composed of lithium-containing sulfides; Carbon fiber, having pores extending inward from the surface, with the core embedded in the carbon fiber and housed within the pores; The carbon fiber is embedded with a plurality of cores, and the plurality of cores form a beaded structure on the carbon fiber.

2. The lithium replenishment material according to claim 1, characterized in that, The core is partially embedded in the carbon fiber and at least partially protrudes from the surface of the carbon fiber; and / or, the core is completely embedded in the carbon fiber and entirely placed within the pore.

3. The lithium replenishment material according to claim 1, characterized in that, The lithium replenishment material also includes a coating layer that covers the outer surface of the core exposed to the external environment.

4. The lithium replenishment material according to claim 1, characterized in that, The core has a distribution density of 10 g / cm³ on a single carbon fiber. 3 ~15g / cm 3 ; and / or the carbon fiber accounts for 1% to 5% of the mass of the lithium supplement material.

5. The lithium replenishment material according to claim 1, characterized in that, The particle size D50 of the core is 5nm~80nm; and / or the diameter of the carbon fiber is 20nm~100nm; and / or the length of the carbon fiber is 1μm~20μm.

6. The lithium replenishment material according to claim 1, characterized in that, The pores are spherical, hemispherical, or ellipsoidal in shape; and / or the pore diameter is 5 nm to 80 nm; and / or the volume of the pores accounts for 40% to 70% of the volume of the carbon fiber.

7. The lithium replenishment material according to claim 3, characterized in that, The thickness of the coating layer is 10 nm to 100 nm; and / or, the mass percentage of the coating layer in the lithium replenishment material is 2% to 5%.

8. The lithium replenishment material according to claim 1, characterized in that, The chemical formula of the lithium-containing sulfide includes Li x S y , where 1≤x≤2, 1≤y≤6.

9. A method for preparing a lithium-supplementing material, characterized in that, The preparation method is used to prepare the lithium supplementation material according to any one of claims 1-8, and the preparation method includes: A precursor mixture is obtained by mixing a lithium sulfide precursor, a polymer precursor, and a carbon fiber precursor and then shaping it. The lithium replenishing material is obtained by sintering the precursor mixture. The lithium replenishing material includes a core and carbon fibers. The carbon fibers have pores extending from the surface inward. The core is embedded in the pores of the carbon fibers.

10. The method for preparing the lithium-supplementing material according to claim 9, characterized in that, After sintering the precursor mixture to obtain the lithium-supplementing material, the process further includes: After the lithium replenishment material and carbon source are mixed and sintered, the carbon source forms a coating layer that covers the outer surface of the core exposed to the external environment.

11. A positive electrode plate, characterized in that, The positive electrode includes a current collector and an active material layer disposed on the current collector. The active material layer includes a positive electrode material and a lithium supplement material as described in any one of claims 1-8, or the active material layer includes a positive electrode material and a lithium supplement material obtained by the preparation method of the lithium supplement material as described in claim 9 or 10.

12. A secondary battery, characterized in that, The battery may include the positive electrode sheet as described in claim 11, or the battery may include the lithium replenishing material as described in any one of claims 1-8, or the battery may include the lithium replenishing material obtained by the method for preparing the lithium replenishing material as described in claim 9 or 10.

Citation Information

Patent Citations

  • Method for uniformly coating carbon on nano lithium iron phosphate

    CN101944601A

  • Method for preparing lithium carbide / lithium sulfide composite anode material of lithium-sulfur battery by performing carbon thermal reduction on lithium sulfate

    CN106229487A